2016
DOI: 10.1136/ejhpharm-2016-001019
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing errors from look-alike drug trade names

Abstract: ObjectivesTo improve patient safety, we investigated near-miss dispensing errors in our hospital and evaluated the effectiveness of specific preventive strategies.MethodsThe incidence and type of near-miss dispensing errors in a single hospital in Taiwan were identified in 2013. The causes of dispensing errors were analysed by consensus of an expert panel comprising a senior pharmacist on duty, a group leader in the pharmacy and an author. Because alphabetical trade names were routinely used in our pharmacy, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 19 publications
0
40
0
2
Order By: Relevance
“…Os fatores mais comuns encontrados em outras pesquisas foram: alta carga de trabalho, baixo número de funcionários, confusão com nomes e sons parecidos/similares, falta de conhecimento/experiência da equipe da farmácia, pressa e interrupções/distrações. Entretanto, estes fatores foram apontados a partir de relatos subjetivos, entrevistas e/ou formulários de notificação de incidentes [13][14][15][16][17][18] .…”
Section: Discussionunclassified
“…Os fatores mais comuns encontrados em outras pesquisas foram: alta carga de trabalho, baixo número de funcionários, confusão com nomes e sons parecidos/similares, falta de conhecimento/experiência da equipe da farmácia, pressa e interrupções/distrações. Entretanto, estes fatores foram apontados a partir de relatos subjetivos, entrevistas e/ou formulários de notificação de incidentes [13][14][15][16][17][18] .…”
Section: Discussionunclassified
“…Six of the included studies utilised a pre and post-intervention methodology with prospective observations, [24][25][26][30][31][32] four were parallel arm prospective observational studies 22,[27][28][29] and one was a multi-phase prospective observational study. 23 The data collection periods ranged from 6 days to 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of studies used a research pharmacist observer who identified dispensing errors independent to the dispensing process, 22,[24][25][26][27]30 while others incorporated the identification and documentation of dispensing errors into the final verification stage of the dispensing process. 23,24,29,31,32 In all but one study, those evaluating the presence of dispensing errors were not blinded to the study allocation of the medication orders or prescriptions being assessed. One study utilised a blinded research pharmacist to review dispensed items after completion of the final verification by pharmacy staff.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, major problems remain in drug identification: many drugs look alike; drugs are relatively small in size; and a large number of drugs need to be identified. Existing identification solutions still have their limitations [5][6][7].…”
Section: Introductionmentioning
confidence: 99%